Analisis Pergeseran Sumber Pendapatan Petani Transmigran Di Lahan Pasang Surut (STUDI KASUS DI KABUPATEN INDRAGIRI HILIR RIAU) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Shifting of income source transmigrant farmer in the tidal swamp from rice and palawija to non-rice happened for along time in some resettlement location in Indonesia.This ferwmenon began in 1975, in Centre Kalimantan, South Kalimantan, Jambi, South Sumatera and Riau. This problem related with constraints of low land productivity, limited labour and some problem about pests of crop. The effort of transmigrant farmer was: (1) to change some kinds of crops and cropping pattern